PERJANJIAN PERKAWINAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 - Oken Shahnaz Pramasantya (Jurnal Cakrawala Hukum, 2017)
The Constitutional Court issued Decision Number 69 / PUU-XIII / where the marriage agreement was held after the marriage took place. Why the Constitutional Court allows the making of marriage contracts after marriage takes place. This study analyzes the legal considerations of the Constitutional Court judges in allowing marriage agreements to take place after the marriage takes place in accordance with the values of justice, as well as analyzing the legal implications of property of marriage agreements made after marriage in the event of any one of the injured parties. This research method is normative juridical. Based on the results of the study that the Marriage Agreement made after the marriage took place could potentially cause harm and injustice for third parties. Third-party interests also become unprotected. Regarding the time of entry into force of the Marriage Agreement made after the marriage takes place and in the Decision of the Constitutional Court Number 69 / PUU-XIII / 2015 in its verdict contained in point 1.5. and 1.6. raises a legal uncertainty. Third parties and husbands or wives who are harmed by the making of the Marriage Agreement after marriage take place may claim compensation and cancellation to the District Court.